Naphtha catalytic treatment using aluminum silicate derived from bentonite ore - Mohammed Sabri (College of Education for Pure Sciences, 2008)
ABSTRACT The catalyst was prepared from red bentonite ore after the removal of unreactive materials toward catalysis (carbonate and bicarbonate). This catalyst was used in the catalytic treatment of naphtha from (Baba) Kirkuk . The naphtha was passed to the reactor in the vapour phase and treated at (450, 500 and 550)° C at constant rate. The hydrocarbon composition for the treated naphtha samples were studied by determining the amount of n-paraffins, aromatics and olefinics. Moreover additional measurments of refractive index and density were determined. The chemical structure of n-paraffins were analysed using gas chromatography (GC) depending on the (UOP) standard methods (UOP-690). Olefinic content was also determined using standard American method ASTM-D1492. The paraffins amount increasd up to (48.913%) in the treated naphtha, compared with (39.4065%) in the untreated naphtha. Aromatic hydrocarbons reached up to (22.5773%), compared with 11.8843 % in the untreated naphtha, with the amount of naphthenic to 28.5097 % in the treated naphtha compared with 48.7092 % in the untreated naphtha . The amount of olefinic hydrocarbons increased up to 2.5 % at (550)°C compared with (0.0 %) in the untreated naphtha.